Zakat Institution and Maqasid al-ShariÊ»a: A Study of a Community Empowerment-Based Zakat Program Run by the BAZNAS Bengkulu Province - Toni, Hariya (Al-Risalah, 2020)
This paper discusses a community empowerment-based zakat program run by the BAZNAS (National Amil Zakat Agency) of Bengkulu Province as well as proves the flexibility of the classical maqÄá¹£id al-sharÄ«Ê»a in responding to modern development that have not been analyzed by previous researchers. In addition, this paper argues that institutionalizing zakat is not a "bureaucratization of sharia" as stated by Asep Saepuddin Jahar. This paper uses principles of field studies that are corroborated with relevant literature sources. This paper shows that programs initiated by the BAZNAS of Bengkulu Province such as 'Bengkulu takwa', 'healthy Bengkulu', 'smart Bengkulu', and 'prosperous Bengkulu' are an implementation of maqÄá¹£id al-sharÄ«Ê»a in responding to modern development. These programs demonstrate that preserving religion (al-dÄ«n), soul (al-nafs), intellect (al-Ê¿aql), lineage (al-nasl), and property (al-mÄl) in the classical maqÄá¹£id al-sharÄ«Ê»a discourse is not static, but dynamic. This dynamism can be interpreted as the prosperity of religion, soul, lineage, intellect, and people's property. Thus, this paper argues that institutionalizing zakat is neither a "bureaucratization of sharia" nor merely matching the classical maqÄá¹£id al-sharÄ«Ê»a with the modern context. Furthermore, it is a waá¹£Ä«la for the welfare of the people in a structured and measured manner.